Gender Variance in Childhood and Sexual Orientation in Adulthood: A Prospective Study. (28th March 2012) - Steensma, Thomas D.; van der Ende, Jan; Verhulst, Frank C.; Cohen‐Kettenis, Peggy T.
ABSTRACT: Introduction.  Several retrospective and prospective studies have reported on the association between childhood gender variance and sexual orientation and gender discomfort in adulthood. In most of the retrospective studies, samples were drawn from the general population. The samples in the prospective studies consisted of clinically referred children. In understanding the extent to which the association applies for the general population, prospective studies using random samples are needed. Aim.  This prospective study examined the association between childhood gender variance, and sexual orientation and gender discomfort in adulthood in the general population. Methods.  In 1983, we measured childhood gender variance, in 406 boys and 473 girls. In 2007, sexual orientation and gender discomfort were assessed. Main Outcome Measures.  Childhood gender variance was measured with two items from the Child Behavior Checklist/4–18. Sexual orientation was measured for four parameters of sexual orientation (attraction, fantasy, behavior, and identity). Gender discomfort was assessed by four questions (unhappiness and/or uncertainty about one's gender, wish or desire to be of the other gender, and consideration of living in the role of the other gender). Results.  For both men and women, the presence of childhood gender variance was associated with homosexuality for all four parameters of sexual orientation, but not with bisexuality. The report of adulthood homosexuality was 8 to 15 times higher for participants with a history of gender variance (10.2% to 12.2%), compared to participants without a history of gender variance (1.2% to 1.7%). The presence of childhood gender variance was not significantly associated with gender discomfort in adulthood. Conclusions.  This study clearly showed a significant association between childhood gender variance and a homosexual sexual orientation in adulthood in the general population. In contrast to the findings in clinically referred gender‐variant children, the presence of a homosexual sexual orientation in adulthood was substantially lower.Steensma TD, van der Ende J, Verhulst FC, and Cohen‐Kettenis PT. Gender variance in childhood and sexual orientation in adulthood: A prospective study. J Sex Med 2013;10:2723–2733.